2012
DOI: 10.1111/j.1349-7006.2012.02315.x
|View full text |Cite
|
Sign up to set email alerts
|

Villin 1 is a predictive factor for the recurrence of high serum alpha‐fetoprotein‐associated hepatocellular carcinoma after hepatectomy

Abstract: The prognostic assessment of patients with hepatocellular carcinoma (HCC) after resection is an important clinical issue. The present study investigated those genes associated with high serum alpha-fetoprotein (AFP), and their clinical significance, including prognosis and recurrence after hepatectomy. Based on gene expression analysis of 110 training HCC cases, 20 genes whose mRNA expression levels were significantly upregulated and 50 genes that were downregulated correlated with high serum AFP-associated HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…VIL1 was useful for distinguishing normally differentiated epithelial cells from the simple epithelia lining the gastrointestinal tract (41). Upregulation of VIL1 was observed in HCC tissues (42). VIL1 may be a biomarker of metastatic adenocarcinomas.…”
Section: Discussionmentioning
confidence: 85%
“…VIL1 was useful for distinguishing normally differentiated epithelial cells from the simple epithelia lining the gastrointestinal tract (41). Upregulation of VIL1 was observed in HCC tissues (42). VIL1 may be a biomarker of metastatic adenocarcinomas.…”
Section: Discussionmentioning
confidence: 85%
“…Among these DEGs, 151 were upregulated and 292 were downregulated in FLHS chickens compared to healthy hens. The top 10 upregulated and downregulated genes are indicated in Figure 2B , including OVCH2 ( Wang and Ma, 2019 ), ANKRD22 ( Yin et al, 2017 ), ENSGALG00000005043 ( Moreira et al, 2018 ), SLC6A9 ( Alfadhel et al, 2016 ), NMRAL1 ( Garciandia and Suarez, 2013 ), RASGRP3 ( Oh-hora et al, 2003 ), SLC38A1 ( Kondoh et al, 2007 ), ANGPTL4 ( La Paglia et al, 2017 ; Singh et al, 2018 ), AOC1 ( Iffiu-Soltesz et al, 2010 ), PDE4D ( Yun et al, 2016 ), ADAMTS17 ( Mead and Apte, 2018 ), VIL1 ( Xieraili et al, 2012 ; Roy et al, 2018 ), FAH ( Grompe, 2017 ), and SPON2 ( Zhang Y. L. et al, 2018 ), which have been reported as involved in the regulation of inflammatory processes and lipid metabolism ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Upregulation of villin-1 in high serum ␣-fetoprotein-associated HCC tumor tissues has been correlated with high serum PIVKAII, poor differentiation, vascular invasion, an advanced stage of cancer, and the absence of recurrence. Patients with early HCC recurrence displayed upregulated villin-1 more frequently than patients with late recurrence (49). Considering the known functions of villin-1, it likely takes part in the development of HCC and could be as a marker of postoperative recurrence and poor prognosis of HCC.…”
Section: Discussionmentioning
confidence: 97%